2018
DOI: 10.1515/jpm-2018-0271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical chorioamnionitis at term IX: in vivo evidence of intra-amniotic inflammasome activation

Abstract: Background The inflammasome has been implicated in the mechanisms that lead to spontaneous labor at term. However, whether the inflammasome is activated in the amniotic cavity of women with clinical chorioamnionitis at term is unknown. Herein, by measuring extracellular ASC [apoptosis-associated speck-like protein containing a C-terminal caspase recruitment domain (CARD)], we investigated whether there is in vivo inflammasome activation in amniotic fluid of patients with clinical chorioamnionitis at term with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 153 publications
(180 reference statements)
2
31
0
Order By: Relevance
“…In the current study, we found that preterm PROM patients with a positive culture and intra-amniotic inflammation (diagnosed as the elevated amniotic fluid concentration of IL-6 >2.6 ng/mL) have elevated bacterial burden using 16S rRNA gene qPCR. These results are consistent with previous studies in which women with preterm labor [29,82], clinical chorioamnionitis at term [116] or preterm PROM [31,32] and proven intra-amniotic infection display higher levels of IL-6 than those with intra-amniotic inflammation without detectable microorganisms. Patients with a positive culture do not seem to display differences in the intensity of the intra-amniotic inflammatory response, as evidenced by amniotic fluid IL-6 concentrations.…”
Section: Microbial Detection and Intra-amniotic Infectionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, we found that preterm PROM patients with a positive culture and intra-amniotic inflammation (diagnosed as the elevated amniotic fluid concentration of IL-6 >2.6 ng/mL) have elevated bacterial burden using 16S rRNA gene qPCR. These results are consistent with previous studies in which women with preterm labor [29,82], clinical chorioamnionitis at term [116] or preterm PROM [31,32] and proven intra-amniotic infection display higher levels of IL-6 than those with intra-amniotic inflammation without detectable microorganisms. Patients with a positive culture do not seem to display differences in the intensity of the intra-amniotic inflammatory response, as evidenced by amniotic fluid IL-6 concentrations.…”
Section: Microbial Detection and Intra-amniotic Infectionsupporting
confidence: 93%
“…Herein, we showed that there is a significant correlation between 16S rRNA gene signal, microbial burden, and extracellular ASC concentrations in amniotic fluid of patients with preterm PROM. Extracellular ASC has been previously utilized as an in vivo indicator of inflammasome activation in amniotic fluid [82,115,116]. Indeed, we have recently demonstrated that the concentrations of this protein are increased in the amniotic cavity during the sterile physiological process of spontaneous labor at term [115], as well as in pathological processes such as clinical chorioamnionitis at term [116] and preterm labor/ birth [82].…”
Section: Microbial Burden Correlated With Intra-amniotic Inflammasomementioning
confidence: 97%
See 2 more Smart Citations
“…ABSTRACT: Cell-free DNA (cfDNA) in blood, urine and other biofluids provides a unique window into 24 human health. A proportion of cfDNA is derived from bacteria and viruses, creating opportunities for the 25 diagnosis of infection via metagenomic sequencing.…”
mentioning
confidence: 99%